Assessment of the Processing Effects of Fresh Solanum Anguivi Berries on Biochemical Contents and Functional Properties of Powder - BAMBA, Bio Sigui Bruno; AKRE, Marie Stella Hermance; KONAN, N’Guessan Ysidor; KOMENAN, Ayemene Cedrick Ardin; N’GOUIN, Joelle-Annabelle; SORO, Yade Rene (Journal of Food Technology Research, 2020)
Solanum anguivi is used as food and medicine for numerous health-benefiting effects. However, it is highly perishable due to its high moisture content. To avoid post-harvest losses, sun-drying is the common preservation method used from tropical countries. Unfortunately, this method faces uncomfortable applying during harvest period usually holding in rainy seasons. This study aims to investigate the effect the of oven-drying temperature (60, 80, and 100°C) combining with or not blanching (80 °C for 10 min) compared to the sun-drying on biochemical contents (moisture, crude fiber, polyphenol, alkaloid content) and functional properties (solubility, hygroscopicity) of S. anguivi berries processed into powder. The results exhibited excellent nutritional quality of S. anguivi powder processed from the oven-drying compared to the sun-drying. In addition, the increase in oven-drying temperature significantly affected all studied properties. Sun-drying resulted in long drying delay and powder with low polyphenol content. Moreover, blanching enhanced drying effect and resulted in powder having high polyphenol and fiber content but showing low solubility and hygroscopicity. Nonetheless, oven-drying berries at 80 °C for 24h without blanching proved to be the optimal condition leading to good quality powder which demonstrated high solubility and low hygroscopicity suggesting its good utilization and preservation as functional food ingredient.